The Love Curriculum Approach in Overcoming Learning Loss in Primary and Secondary Schools: A Review of the Literature and Implications of Islamic Education - Sari, Windy Dian (At-tadzkir: Islamic Education Journal, 2025)
Learning loss as a result of the COVID-19 pandemic has become a serious challenge in the world of education, especially at the elementary and secondary school levels. This article aims to examine the potential  of the Love Curriculum approach  as an innovative solution in overcoming learning loss. Using the literature review method, this article analyzes various relevant literature related to compassion-based curriculum, affective pedagogy, and humanistic approaches in education. The results of the study show that the Love Curriculum approach that emphasizes the value of empathy, attention, and positive teacher-student relationships can improve the learning climate, increase motivation, and recover students' academic and social-emotional lags. The practical implications of this study point to the importance of teacher training, strengthening value-based curriculum, and collaboration between schools and parents to create a loving learning environment. This article recommends the implementation of the Love Curriculum as a complementary strategy in national learning recovery policies. These findings are expected to be a conceptual contribution to the development of a more humane and transformative educational model in the post-pandemic era.